Surgical outcomes for esophageal atresia at Hue Central Hospital - Nguyen, Thanh Xuan (Tạp chí Y Dược Huế, 2025)
Background: Esophageal atresia is a congenital defect that requires prompt surgical treatment. Despite advances in neonatal care and surgical techniques, complications and mortality remain significant, especially in cases with other congenital anomalies. Few studies have evaluated esophageal atresia treatment results in Vietnam. Objective: This study aims to investigate the clinical features and treatment outcomes of esophageal atresia at Hue Central Hospital. Materials and method: 32 children diagnosed with esophageal atresia who underwent surgical repair at Hue Central Hospital from March 2019 to December 2023 were included. Data were collected from medical records, including demographics, clinical presentation, surgical procedures, postoperative complications, and treatment outcomes. Descriptive statistics were used, and complications were classified using the Clavien-Dindo system. Results: The study included 15 males and 17 females. The average gestational age was 36.6 ± 2.3 weeks, and the mean birth weight was 2256.3 ± 240.9 grams. Surgery was performed an average of 4.7 ± 3.2 days after birth. Type C esophageal atresia was the most common subtype, while 6.2% had Type A. Primary anastomosis was done in 90.6% of cases, and 9.4% required staged repair. The average hospital stay was 25.4 ± 15.7 days. Postoperative complications occurred in 43.7% of patients, with anastomotic stricture, pneumonia, and anastomotic leakage being the most common. The overall mortality rate was 15.6%, with 3 deaths due to cardiac anomalies and 2 due to respiratory problems. 71.9% of patients were discharged in stable condition. Conclusion: 84.4% survival rate observed in this study showed positive results in resource-limited settings. Prompt diagnosis, timely surgical intervention, and enhanced perioperative management are essential for improving outcomes in esophageal atresia. Further research is needed to refine the approach to managing esophageal atresia.